Analyzing impact of competitive dimensions on the efficiency of e-learning: دراسه استطلاعيه (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The aim of this research is to diagnose the impact of competitive dimensions represented by quality, cost, time, flexibility on the efficiency of e-learning, The research adopted the descriptive analytical method by identifying the impact of these dimensions on the efficiency of e-learning, as well as the use of the statistical method for the purpose of eliciting results. The research concluded that there is an impact of the competitive dimensions on the efficiency of e-learning, as it has been proven that the special models for each of the research hypotheses are statistically significant and at a level of significance of 5%, and that each of these dimensions has a positive impact on the dependent variable, and the research recommended the necessity of applying e-learning because of the importance of In solving the problem of the explosion of knowledge and the increasing demand for education, the expansion of admission opportunities in education and the elimination of traditional education problems, he also recommended the need to work on activating the competitive dimensions as one of the means that leads to enhancing the efficiency of e-learning.